PENGARUH KOMPENSASI, MOTIVASI, DAN DISIPLIN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BANK PERKREDITAN RAKYAT RONABASA BALIKPAPAN - Pakpahan, Niken Theresia; Yusuf, Tamzil; Yuliani, Tutik (MEDIA RISET EKONOMI [MR.EKO], 2024)
The purpose of this research is to determine the influence of compensation, motivation, and discipline on employee job satisfaction at PT Bank Perkreditan Rakyat Ronabasa Balikpapan. The sampling technique in this study is a census with a sample of 46 employees. Data collection was conducted using questionnaires, and SmartPLS was utilized for data analysis. The findings reveal that compensation has a positive and significant impact on employee job satisfaction at PT Bank Perkreditan Rakyat Ronabasa Balikpapan. The motivation variable has a positive and significant impact on employee job satisfaction at PT Bank Perkreditan Rakyat Ronabasa Balikpapan. The discipline variable has a positive and significant impact on  employee job satisfaction at PT Bank Perkreditan Rakyat Ronabasa Balikpapan. The most dominant variable is motivation.